Long Noncoding RNA ANRIL: Lnc-ing Genetic Variation at the Chromosome 9p21 Locus to Molecular Mechanisms of Atherosclerosis - Holdt, Lesca M.; Teupser, Daniel (Frontiers in Cardiovascular Medicine, 2018)
Ever since the first genome-wide association studies (GWAS) on coronary artery disease (CAD), the Chr9p21 risk locus has emerged as a top signal in GWAS of atherosclerotic cardiovascular disease, including stroke and peripheral artery disease. The CAD risk SNPs on Chr9p21 lie within a stretch of 58 kilobases of non-protein-coding DNA, containing the gene body of the long noncoding RNA (lncRNA) antisense non coding RNA in the INK4 locus (ANRIL). How risk is affected by the Chr9p21 locus in molecular detail is a matter of ongoing research. Here we will review recent advances in the understanding that ANRIL serves as a key risk effector molecule of atherogenesis at the locus. One focus of this review is the shift in understanding that genetic variation at Chr9p21 not only affects the abundance of ANRIL, and in some cases expression of the adjacent CDKN2A/B tumor suppressors, but also impacts ANRIL splicing, such that 3’-5’-linked circular noncoding ANRIL RNA species are produced. We describe how the balance of linear and circular ANRIL RNA, determined by the Chr9p21 genotype, regulates molecular pathways and cellular functions involved in atherogenesis. We end with an outlook on how manipulating circular ANRIL abundance may be exploited for therapeutic purposes.